An exploratory study of pro-inflammatory cytokines in individuals with alcohol use disorder: MCP-1 and IL-8 associated with alcohol consumption, sleep quality, anxiety, depression, and liver biomarkers - Kazmi, Narjis; Wallen, Gwenyth R.; Yang, Li; Alkhatib, Jenna; Schwandt, Melanie L.; Feng, Dechun; Gao, Bin; Diazgranados, Nancy; Ramchandani, Vijay A.; Barb, Jennifer J. (Frontiers in Psychiatry, 2022)
Background: High levels of sleep disturbances reported among individuals with alcohol use disorder (AUD) can stimulate inflammatory gene expression, and in turn, may alter pro-inflammatory cytokines levels. We aimed to investigate associations between pro-inflammatory cytokine markers with subjective measures of sleep quality, psychological variables and alcohol consumption among individuals with AUD. Methods: This study is comprised of AUD cases (n =50) and healthy volunteers (n =14). Spearman correlation was used to investigate correlations between plasma cytokine levels and clinical variables of interest (liver and inflammatory markers, sleep quality, patient reported anxiety/depression scores, and presence of mood and/or anxiety disorders (DSM IV/5); and history of alcohol use variables. Results: The AUD group was significantly older, with poorer sleep quality, higher anxiety/depression scores, and higher average drinks per day as compared to controls. Within cases, IL-8, IL-17A and MCP-1 had positive significant correlations with sleep, anxiety, depression and drinking variables. Specifically, higher levels of MCP-1 were associated with poorer sleep (p=.004), higher scores of anxiety (p=.006) and depression (p <.001), and higher number of drinking days (p =.002), average drinks per day (p <.001), heavy drinking days (p <.001) and total number of drinks (p <.001). The multiple linear regression model for MCP-1 showed that after controlling for sleep status and heavy drinking days, older participants (p = .003) with more drinks per day (p = .016), and higher alkaline phosphatase level (p = .001) had higher MCP-1 level. Conclusion: This exploratory analysis revealed consistent associations with cytokines IL-17A, MCP-1 and IL-8 and drinking consumption, sleep quality, and anxiety and depression in cases. Furthermore, inflammatory and liver markers were highly correlated with certain pro-inflammatory cytokines in the cases indicating a bidirectional relationship between chronic alcohol use and inflammation. These associations may contribute to prolonged inflammatory responses and potentially higher risk of co-morbid chronic diseases.